A Decidability Theorem - Filippovski, Vitaly (Analytica, 2022)
The aim of this paper is to present the proof of the decidability theorem that says that for every ω-consistent recursive class r of formulas, for all recursive class signs r υ Gen r belongs to Flg(k) whereas Neg(υ Gen r) does not belong to Flg(k) (where υ is the free variable of r).